Double chocolate cookie murder - Delaney, Devon (Delaney, Devon. Cook-off mystery., 2021)
"When her old high school home ec teacher is murdered, with prizes for the big cookie contest next to his body, Sherry Oliveri must figure out which of the contestants is stirring up trouble"--